Increasing the Yield of Powder and Bioactive Materials during Extraction and Spray Drying of Dragon Fruit Skin Extracts - Dian Shofinita; Yazid Bindar; Tjokorde Walmiki Samadhi; Najwa Shufia Choliq; Arwinda Aprillia Jaelawijaya (Institute for Research and Community Services, Institut Teknologi Bandung, 2021)
One potential utilization of dragon fruit skin is to produce bioactive materials as natural antioxidants and colorants for the food industry by extraction and spray drying. This study investigated the quality (total phenolic compounds/TPC, betacyanin and betaxanthin contents, and antioxidant activity) of the extracts and spray-dried products, and the quantity (powder yield) obtained by the use of different types and amounts of spray drying agents. Two drying agents were introduced during spray drying, i.e. maltodextrin and whey protein isolate (WPI). The result showed that a lower extraction solvent to solid ratio may result in a lower yield of TPC, betacyanin and betaxanthin contents, and also in antioxidant activity of the dragon fruit skin extract. In addition, maltodextrin and WPI were found to be able to significantly increase the yield from spray drying. The highest yield (72.7 ± 8.4%) was obtained with the use of 40% maltodextrin as drying agent, while the control yielded 9.5 ± 1.8%. Furthermore, it was found that the spray-dried product could recover more than 90% of the TPC and betacyanin in the extracts, which indicates that spray drying may be suitable for heat-sensitive materials.